Internal Rotation Stress Testing Improves Radiographic Outcomes of Type 3 Supracondylar Humerus Fractures. Issue 1 (January 2019) - Bauer, Jennifer M.; Stutz, Christopher M.; Schoenecker, Jonathan G.; Lovejoy, Steven A.; Mencio, Gregory A.; Martus, Jeffrey E.
Abstract : Background: The purpose of this study was to determine if routine use of an intraoperative internal rotation stress test (IRST) for type 3 supracondylar humerus fractures will safely improve maintenance of reduction. Methods: An intraoperative protocol for type 3 supracondylar humerus fractures was adopted at our institution, consisting of fracture reduction, placement of 2 laterally based divergent pins, and then an IRST to determine the need for additional fixation with a medial column pin placed through a small open approach. Fractures treated with the prospective IRST protocol were compared with a retrospective cohort before adoption of the protocol (pre-IRST). The primary outcomes were differences in Baumann's angle, lateral humerocapitellar angle, and the rotation index between final intraoperative fluoroscopic images and radiographs at final follow-up. Secondary outcomes were complications such as iatrogenic nerve injury, loss of fixation, or need for reoperation. Results: There were 78 fractures in the retrospective cohort (pre-IRST) and 49 in the prospective cohort (IRST). Overall rotational loss of reduction (>6%), measured by lateral rotation percentage, and major rotational loss of reduction (>12%) were less common in the IRST cohort (6/49 vs. 27/78, P =0.007 overall; 0/49 vs. 8/78, P =0.02 major loss). There were no major losses of reduction for Baumann's angle (>12 degrees) in either cohort. There were 5 subjects in the pre-IRST cohort (6.4%) with a major loss of reduction of the humerocapitellar angle (>12 degrees) and none in the IRST cohort ( P =0.16) Loss of proximal fixation with need for reoperation occurred in 3 fractures in the pre-IRST cohort, and none in the IRST cohort ( P =0.28). There were no postoperative nerve injuries in either group. Conclusions: Intraoperative IRST after placement of 2 lateral pins assists with the decision for additional fixation in type 3 supracondylar humerus fractures. This method improved the final radiographic rotational alignment, and was safely performed using a mini-open approach for medial pin placement. Level of Evidence: Level III—prospective cohort compared with a retrospective cohort.